Mobile Application for Market Data Collection of Property Tax Object - Devriady Pratama (LPPM Universitas Islam 45 Bekasi, 2025)
This research focuses on designing a mobile application for collecting property market data to support Land Value Zone (ZNT) analysis for local governments. Currently, market data collection processes are often conducted manually, which is time-consuming, resource-intensive, and prone to subjectivity. The proposed application leverages mobile technology to enhance the efficiency and effectiveness of field data collection with features such as user authorization, geographic data storage, and multimedia data storage, including images. The research adopts the prototyping method, involving direct interaction between developers and users. Testing results indicate that the application performs its functions effectively and facilitates data collection based on Geospatial Information Systems (GIS). This study suggests further development for other mobile platforms and modules for price analysis based on ZNT.